Overcoming Obstacles in Global Requirements Elicitation : A Multicultural Perspective - Siakas, Kerstin; Georgiadou, Elli; Rahanu, Harjinder; Siakas, Errikos; Meggoudis, Nick; Siakas, Dimitrios (Brazilian Computer Society, 2024)
Nowadays, multiculturality is the norm. No country or organization is monocultural. Little previous work has been carried out specifically on how culture influences multicultural requirements elicitation. In this paper we look at the importance of culture with the aim of increasing understanding of the role of cultural differences in differences in multicultural requirements elicitation. This paper starts with a literature review demonstrating the importance of raising awareness and understanding of cultural diversity which often causes conflict and mistrust which can lead to failure of any project. The ultimate aim is the improvement of the whole systems development process as well as the resulting products and services. We present the development and validation of the Multicultural Requirements Elicitation [McRE) framework which helps prevent or at least minimize prejudice, conflicts, misunderstandings and misinterpretations arising from cultural differences. McRE is an instrument for carrying out processes, defining the purpose of these processes and the methods that must be used, as well practical suggestions for raising awareness of cultural diversity and reflecting on unconscious bias. Additionally, McRE suggests relevant training and learning. Finally, it advocates prevention and mitigation actions. The rationale and results from the validation of the framework by experts from industry and academia are presented. The validation provided strong indications that the McRE framework is both necessary and suitable for multicultural requirements elicitation in the software development process but also in other domains.
Keywords: Requirements Elicitation; Multicultural Requirements Elicitation; Process Improvement; McRE; GSE; culture; fi=Tuotantotalous|en=Industrial Management|